2013
DOI: 10.1136/bmjopen-2013-003007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of recovery time after acute peripheral facial palsy: a prospective cohort study

Abstract: ObjectiveOwing to a lack of prospective studies, our aim was to evaluate diagnostic factors, in particular, motor and non-motor function tests, for prognostication of recovery time in patients with acute facial palsy (AFP).DesignProspective cohort study.SettingUniversity hospital.Participants259 patients with AFP.MeasurementsClinical data, facial grading, electrophysiological motor function tests and other non-motor function tests were assessed for their contribution to recovery time.ResultsThe predominant ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 24 publications
2
68
1
7
Order By: Relevance
“…Studies carried out with an invasive EMG, which is a more accurate procedure for muscle evaluation, indicated that the healthy human face may present up to 6% of symmetry during the production of facial expressions (21) . The acute unilateral facial palsy is the most common disease of the facial nerve (19) . Most of those cases end up being diagnosed as idiopathic facial paralysis (Bell's palsy), once the cause of the disease is not identified, with an early use of oral steroids as a traditional medical treatment (12,24) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies carried out with an invasive EMG, which is a more accurate procedure for muscle evaluation, indicated that the healthy human face may present up to 6% of symmetry during the production of facial expressions (21) . The acute unilateral facial palsy is the most common disease of the facial nerve (19) . Most of those cases end up being diagnosed as idiopathic facial paralysis (Bell's palsy), once the cause of the disease is not identified, with an early use of oral steroids as a traditional medical treatment (12,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Most of those cases end up being diagnosed as idiopathic facial paralysis (Bell's palsy), once the cause of the disease is not identified, with an early use of oral steroids as a traditional medical treatment (12,24) . The great challenge of the studies is in determining prognosis indicators for the probability and time of recovery for patients, as the existing studies have low casuistry and are mostly retrospective (19) . It is known that much more than the underlying cause for paralysis, the severity of the damage to the facial nerve is crucial in the recovery of movements (19) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although with less evidences, other rehabilitative approaches, such as physical therapy, biofeedback therapy, relaxation exercises with massages therapy, coordination and facial expression exercises, can reduce muscle stiffness, facilitating facial movements. Relatively to acupuncture and electrical nerve stimulation (in order to accelerate healing by stimulating muscle), there are still not enough data in the literature in order to [32] Ramsay Hunt syndrome Intravenous steroids as soon as possible 75% recovery at 6 mo if treated within 3 d from onset; 30% recovery at 6 mo if treated after 7 d from onset [36,44] Temporalis elongation mioplasty 80% recovery within 1 mo [38] Gracilis muscle microvascular free flap 89% recovery within 4-6 mo [45] Sural nerve grafting N/A Cross-facial nerve grafting 83% recovery within 1 yr [46] Rehabilitation approaches Botulinum toxin 100% recovery (temporary) [24] Physiotherapy Ciorba A et al . Facial palsy in children certify the real efficacy [15,[24][25][26][27] .…”
Section: Rehabilitation Approachesmentioning
confidence: 99%